The singular epidemiology of HPV infection among French Guianese women with normal cytology - Antoine Adenis; Valentin Dufit; Maylis Douine; Fatiha Najioullah; Vincent Molinie; Dominique Catherine; Odile Kilié; Nadia Thomas; Jean Luc Deshayes; Paul Brousse; Hatem Ben Amor; Remy Pignoux; et al. (BMC, 2017)
Abstract Background In French Guiana, cervical cancer is the second most frequent cancer in females. The objective of the present study was to describe the prevalence of HPV infections in women with normal cervical cytology living in the remote villages of French Guiana. Methods Before the study, the study team communicated in the remote villages on the importance of screening. All women from the target population were offered to participate. They signed informed consent during inclusion and then had a concomitant HPV-test and cervical smear. Only women with normal cytology and a good quality smear were analyzed. The detection of HPV-DNA was performed using the GREINER-BIO-ONE kit. Results Overall, 27.2% of women with normal cervical cytology had a positive HPV-test. There was a U-shaped evolution of prevalence with women over 50 years having the highest HPV prevalence, followed by the 20 to 29 years group. The most prevalent HPV genotypes were HPV 53(3.52%), 68(3.33%), 52(2.59%), 31(2.22%) and 16 (1.85%). The proportion of HPV 16 among HPV-infected women was 6.8%. Conclusions HPV prevalence in cytologically normal women was very high. The most prevalent genotypes were very different from what is usually described in the world, and notably in South America.